Laminin receptor 37/67LR regulates adhesion and proliferation of normal human intestinal epithelial cells. - Taoufik Khalfaoui; Jean-François Groulx; Georges Sabra; Amel GuezGuez; Nuria Basora; Patrick Vermette; Jean-François Beaulieu (PLoS ONE, 2013)
Interactions between the cell basal membrane domain and the basement membrane are involved in several cell functions including proliferation, migration and differentiation. Intestinal epithelial cells can interact with laminin, a major intestinal basement membrane glycoprotein, via several cell-surface laminin-binding proteins including integrin and non-integrin receptors. The 37/67kDa laminin receptor (37/67LR) is one of these but its role in normal epithelial cells is still unknown. The aim of this study was to characterise the expression pattern and determine the main function of 37/67LR in the normal human small intestinal epithelium. Immunolocalization studies revealed that 37/67LR was predominantly present in the undifferentiated/proliferative region of the human intestinal crypt in both the immature and adult intestine. Using a human intestinal epithelial crypt (HIEC) cell line as experimental model, we determined that 37/67LR was expressed in proliferative cells in both the cytoplasmic and membrane compartments. Small-interfering RNA-mediated reduction of 37/67LR expression led to HIEC cell-cycle reduction and loss of the ability to adhere to laminin-related peptides under conditions not altering ribosomal function. Taken together, these findings indicate that 37/67LR regulates proliferation and adhesion in normal intestinal epithelial cells independently of its known association with ribosomal function.